Photo-driven bioelectrochemical photocathode with polydopamine-coated TiO2 nanotubes for self-sustaining MoS2 synthesis to facilitate hydrogen evolution - Zeng, L.; Li, X.; Fan, S.; Zhang, M.; Yin, Z.; Tade, Moses; Liu, S. (Elsevier SA, 2019)
© 2018 Elsevier B.V. Developing low-energy and high-efficiency photoelectrocatalysts towards hydrogen evolution reaction is one of the frontier technologies capturing intensive research enthusiasm. In this work, a sustainable solar-driven microbial fuel cell is successfully constructed to synthesize rich edge sites of MoS2 nanomaterials and in situ utilize dual electrons mode for hydrogen generation under visible light illumination (>420 nm). For this photo-driven coupling system, the continuous formation of MoS2 catalyst is more beneficial for efficient hydrogen generation without external bias assistance. Such unique preparation method endows the system to possess more active edge sites for MoS2 exposure, and promotes the obtained materials to exhibit super-hydrophilic behavior. Additionally, the introduction of MoS2 semiconductor could cooperate with bio-electrons to dramatically hinder the recombination of photo-excited electron-hole pairs, leaving more opportunities for photo-electrons to participate hydrogen evolution reaction under the bioelectric field. Simultaneously, the constructed MoS2 based electrode performs excellent photoelectrochemical performance (the onset overpotential only ~36 mV vs. SHE, Tafel slope of 53 mV per decade) and hydrogen evolution activities for hydrogen production with 0.003 m3 m-3 min-1 rate. This work not only leads to a promising approach for the preparation of high efficient photoelectrocatalysts, but also highlights the potential strategy for diverse applications.